TINJAUAN DESAIN SENSORI PADA MUSEUM BANK INDONESIA DALAM MENGAKOMODASI PENGUNJUNG PENYANDANG TUNANETRA - Putri Nadhira Saraswati; Aldyfra L. Lukman (Riset Arsitektur (RISA), 2021)
Abstract- Museum as an architectural object with its function as an educational and recreational facility is open to public and must be able to be used by all people. Therefore, the design of museums must be accessible for all people, including those with special needs. One of the museums in Indonesia which is considered to be a good work of architecture is the Museum of Bank Indonesia. It receives many visitors from various circles, including people with visual impairments. To accommodate visitors with visual impairments, the Museum of Bank Indonesia must have design features that help them to do activities, despite their limited sense of sight. Through this study, the research aims to find out how physical elements in the Museum of Bank Indonesia accommodates the orientation and mobility of visitors with visual impairments. This is a qualitative research, with a descriptive discussion. The collected data are the data on physical elements in the Museum of Bank Indonesia and the data on the behavior of visually impaired visitors while doing orientation and mobility in the Museum of Bank Indonesia exhibition area. The data are collected through observation and interview, then analyzed by using a table which elaborates physical elements from technical requirements aspect and sensory design aspect, and how they accommodate visually impaired visitors. Research shows that some physical elements in the Museum of Bank Indonesia are already adequate in accommodating visually impaired visitors. They able to provide assistance for visually impaired visitors while doing orientation and mobility, as well as gathering information on the museum objects. On the other hand, there are also some physical elements that hinder visually impaired visitors because they don’t technically meet the user’s needs. Therefore, improvement in the physical elements design is needed, so it can accommodate visitors with visual impairments better. Key Words: museum, visual impairment, Bank Indonesia, universal design, sensory design